Encapsulants for light-emitting diodes from visible light-cured epoxy monomers - Schroeder, Walter Fabian (2013)
During the last decade, light-emitting diodes (LEDs) have replaced incandescent, fluorescent, and neon lamps due to their ability to produce high luminosity at low currents and voltages. LEDs are currently encapsulated by thermally curable epoxy resins. However, long periods of curing at high temperature result in high consumption of energy and require stringent process control to avoid failure of the devices. In addition, the thermal cure results in yellowing of the encapsulant, which decreases the efficiency of the LED. In recent years, photoinitiated polymerization has received much interest as it congregates a wide range of economic and ecological benefits. Cationic photoinitiators, such as diaryliodonium salts, generate Brønsted acid in situ, which initiates polymerization. The process can be triggered on demand by irradiating the mixture with light. Results from the present research reveal that cycloaliphatic epoxy monomers, photoactivated with an iodonium salt and Camphorquinone, polymerize readily under visible light irradiation (470 nm) in the absence of external heating. The partial replacement of cycloaliphatic epoxy with aromatic diglycidyl ether of bisphenol-A (DGEBA) is an effective means of improving the refractive index of the material and consequently the efficiency of the photoemission. Visible light polymerization of DGEBA pure proceeds at a slow rate; however, it is enhanced by the increase in temperature during the polymerization of the highly reactive cycloaliphatic monomer. From results obtained in the present research, it may be concluded that visible light polymerization of epoxy monomers is a promising route for the processing of LED encapsulants.